Assessment of diagnostic markers and surgical outcome in horses treated for intestinal colic - JOBAN JOT SINGH; JASMEET SINGH KHOSA; ARUN ANAND; JITENDER MOHINDROO; VANDANA SANGWAN (Indian Journal of Animal Sciences)
To support the decision-making process for the surgical intervention in equine patients suffering from intestinal colic, the present clinical study was conducted on ten horses (5 males and 5 females) aged 3 months to 8 years. An exploratory celiotomy was performed on patients with moderate to severe persistent abdominal pain, a lack of response to treatment, and the absence of intestinal borborygmi. Preoperative physical assessment (heart rate, respiration rate, mucus membrane perfusion, capillary refill time), haemato-biochemical analysis, and peritoneal fluid analysis helped in reaching a decision for surgical intervention as diagnostic indicators. Pre- and post-operative ultrasonography was also performed on the patients. Blood lactate level was significantly higher in non-survivors (9.94 mmol/L) than in survivors (4.32 mmol/L). In survivors, peritoneal fluid showed an increase in degenerative neutrophils, and total protein, and there was a decrease in lactate level post-operatively. Presence of small colon fecolith (n=4) was determined to be the primary cause of colic, followed by pelvic flexure impaction (n=2), caecum impaction (n=1) and right dorsal displacement of large colon (RDDLC) (n=1). Strangulating lesions such as small intestinal volvulus (n=2) was also recorded. The most common post-operative complication was sub-cutaneous seroma (n=2) which subsided on its own in a week or so. Surgical interventions helped to save the lives of 50% of the patients who were successfully discharged from the hospital; remarkably, all of them survived and returned to their normal functionality, as observed in the long-term follow-up.